Sloths in the diet of a Harpy Eagle nestling in eastern Amazon - Galetti, M. [UNESP]; De Carvalho, O. [UNESP] (Wilson Ornithological Society, 2000)
-Prey remains of a nestling Harpy Eagle (Harpia harpyja) over 15 months in eastern Amazon, Brazil included 11 two-toed sloths (Choloepus didactylus), 9 three-toed sloths (Bradypus variegatus), and 1 gray four-eyed opossum (Philander opossum). We found no evidence of predation on primates despite their abundance in the area and their importance to Harpy Eagles studied elsewhere. We observed no sloths in 605 km of line transects, a finding that suggests the inadequacy of transect data to estimate prey density for Harpy Eagles.
Keywords: diet; predation; raptor; Brazil; Bradypus variegatus; Choloepus didactylus; Philander opossum